Construction of a SDN Driven Novel Service System for Operatiors - Jie Liu; Zhe Wang (Dianxin kexue)
In the mobile internet environment, the major service abilities of operators are gradually losing their advantages. The internet service environment requires an open, flexible, operational architecture. Cloud computing and SDN provide ideas and means of service network optimization for operators. Concept and methodology of SDN technology were analyzed, an extension of SDN concept to cover the upper applications, as well as an hierarchical, modular, loosely coupled, virtualization and open service system architecture based on SDN methodology were proposed, aimed at providing some references for further optimization and value-adding of operator's service system.